ПОЛИСЕМИЯ В ЛИНГВИСТИКЕ КАК МНОГОГРАННОЕ И СЛОЖНОЕ ЯВЛЕНИЕ - Tilavova, Malika (Журнал иностранных языков и лингвистики, 2023)
In this article, you'll find a treasure trove of fascinating facts, theories, and interesting examples of the phenomenon of polysemy. It is emphasized in this article that it is only up to you to acquire this wealth spiritually and to develop the ability to use it in practice. The importance of learning polysemous words and the fact that distinguishing them from homonymous words requires great talent is also justified by examples in this article.